دراسة الموسيقي في قصيدة أبي تمام في رثاء محمد بن حميد الطوسي - رحماني, إسحاق; السادات مير قادري, بشرى (قــــــراءات; No 10 (2017): مجلة قراءات, 2019)
يتحدث هذا البحث عن الموسيقي في قصيدة أبي تمام، التي رثي بها محمد بن حميد الطوسي (قائداً من قوّاد المعتصم بالله)، لا نتصور قصيدة تخلو من عناصر الموسيقي إلا وهي تضم في طياتها قسطاً أکبر منها وتعد الموسيقي في الشعر عاملا مهما من العوامل المتعددة التي يشکل الشعر بحيث يفضل بعض الشعراء على البعض بمدی استفادة من الموسيقي . من أشهر قصائد الرثاء في الشعر العربي کلّه،  قصيدة أبي تمام التي يندب فيها البطل الشهيد محمد بن حميد الطوسي، وفيها يصور أثر موته في الناس کما يصف فيها ما کان يتحلی به ذلك القائد والفارس من شجاعة وقوة وکرم. وقد أجاد أبو تمام في اختيار بحر الطويل لقصيدته هذه وقافيته الراء المضمومة، والقصائد الرائية من أکثر القصائد شيوعاً في الشعر العربي نظراً إلى کثرة الكلمات العربية المنتهية بالراء وقافية الراء يتناسب تناسباً تاماً مع مضمون القصيدة التي يدل على الحزن والألم والأسي. يحاول هذه الدراسة لاستعراض الأبعاد المختلفة الموسيقائيّة في قصيدة رثاء محمد بن حميد الطوسي، منها دراسة الموسيقي الخارجية التي تضمنت دراسة الوزن العروضي مع دراسة القافية المستخدمة في القصيدة ودراسة الموسيقي الداخلية التي تضمنت: التکرار والجناس ورد العجز على الصدر، ودراسة الموسيقي المعنوية:  الطباق والمراعاة النظير ويوصلنا البحث إلى نتائج أهمّها: أنّ الموسيقي الناتجة من تكرار الحروف والكلمات والجناس و....ذات صلة وثيقة بأغراض الشاعر وتوحي إلى القارئ حالاته النفسية واستطاع أن يستنفد الموسيقي بنجاح بحيث أن يرفع درجة الموسيقي بکل أنواعه المختلفة إلى الذروة الفنية بحيث أن يضع  المتلقي في تلک الأجواء الحزينة.   Abstract This research investigates the elements of music in Abutamam’s ode in elegy of Mohammed bin Hamid al-Toosi one of the leaders of al-Muʿtaṣim bi’llah, and any ode is not empty of music elements and a great part of the ode be formed by music and the music is an important factor among the many factors that make the poem as far as the use of music is the superiority factor of some poets than other poets. Abutamam’s ode in elegy of martyr hero Mohammed bin Hamid al-Toosi is one of the most famous odes in Arabic poetry, where the impact of his death among people as well as courage, power and forgiveness of that hero and rider is depicted, and Abutamam has acted successfully by the selection of long poem and R rhyme, because to-R ended odes are the most common in Arabic poetry and because of the abundance of many Arabic words that lead to R and R rhyme has a perfect proportion with the content of the ode, which implies the grief, sorrow and sadness. This research investigates the diverse dimensions of music in elegy of Mohammed bin Hamid al-Toosi including outside music that investigates prosodic with used rhyme in the ode and internal music which contains repetition, pun and reiteration and  also spiritual music which contains paradox and parallelism. This research leads us to some results and the most important are the music due to the repetition of letters and words and puns and so on, which has a strong connection with the objectives of the poet and conveys the poet’s inner states to reader and the music has been able to be successful completely, as types of music reach to their highest technical degree and put the reader in the sorrowful atmosphere. Investigation of music in Abutamam’s ode in the elegy of Mohammed bin Hamid al-Toosi   الكلمات الدليلية: الموسيقي الخارجية، الموسيقي الجانبية، الموسيقي الداخلية، الموسيقي المعنوية.